Strategi Peningkatan Kinerja Perusahaan Berdasarkan Keunggulan Kompetitif yang Berkelanjutan dan Perencanaan Sumber Daya (Jurnal Manajemen dan Organisasi, 2019)
Optimization of resources can be achieved by using technology to improve operating performance in order to support the company's business activities. This study was conducted in the implementation of Enterprise Resource Planning (ERP) system in plantation company conducted by PT Kencana Group in 16 subsidiaries, five subsidiaries have implemented ERP as an effort of transformation in using information system. Information and Technology can provide a competitive advantage for the company by adding value to various aspects such as increased operational performance and cost reduction. The research aims to identify the utilization of the company's ERP, ERP implementation measure performance, identify factors that affect the performance of the company, as well as measuring the impact of ERP on business performance. Methods of data analysis used in this research is descriptive and qualitative analyzes to provide a general overview of the study. Inter-variable relationship analysis was done by structural equation modeling (SEM) with partial least square approach using SmartPLS software. Hypothesis test is done by regression analysis to measure the validity and significance of influence of each veriabel, and to estimate the direction and magnitude of its influence respectively. The results showed that there is a significant influence of performance factors of ERP utilization that can affect company performance. Operating performance increased by 1% would increase the net profit margin amounted to 38.7%. Furthermore, enterprise resource planning and sustainable competitive advantage have a positive effect on company performance with general and environmental cost factor significantly less than 0.05. The impact of ERP on the performance of the company has decreased the cost of general expenses. While the impact of SCA on the company's perceived performance at this time is that the environment such as the acreage still has not reached the hectare per staple, and the standard number of labor has not been in accordance with the normative of the garden area.